2007
DOI: 10.1007/bf02893499
|View full text |Cite
|
Sign up to set email alerts
|

Gender-related hormonal risk factors for oral cancer

Abstract: Oral cancer (OC) is a neoplasm with fairly high male to female ratio in most populations. The conspicuously lower incidence of this tumor among women than man is suggestive of certain endocrine involvement in its development. The aim of the present case-control study was to clarify the origin of this gender-specific risk of OC incidence. 2660 inpatients (530 females and 2130 males) with squamous cell OC at the Department of Oral and Maxillofacial Surgery were included in a case-control study. Smoking, alcohol … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
63
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(69 citation statements)
references
References 42 publications
5
63
0
1
Order By: Relevance
“…This suggests that estrogen deficiency may play a role in the pathogenesis of OSCC in some women. [27] The results of this study support previous findings from South Africa [16,28] and from the USA [24] that there are significant differences between black and white persons with OSCC with regard to clinical, epidemiological, and histopathological features of the disease; that black persons are diagnosed with OSCC at a younger age than white persons; [28] and that OSCC affects black males, white males, white females, and black females in a declining order of frequency [ Table 1]. …”
Section: Discussionmentioning
confidence: 97%
“…This suggests that estrogen deficiency may play a role in the pathogenesis of OSCC in some women. [27] The results of this study support previous findings from South Africa [16,28] and from the USA [24] that there are significant differences between black and white persons with OSCC with regard to clinical, epidemiological, and histopathological features of the disease; that black persons are diagnosed with OSCC at a younger age than white persons; [28] and that OSCC affects black males, white males, white females, and black females in a declining order of frequency [ Table 1]. …”
Section: Discussionmentioning
confidence: 97%
“…The incidence rates for cancer of the lip, oral cavity and pharynx (C00-14, excluding C11) as well as the larynx (C32) are increasing among women globally, which could be due to access to better diagnostic aids or changes in the socially acceptable behaviour pattern among women in many other parts of the world such as India [32,33] . Apart from the traditional risk factors discussed above, it has been suggested that oestrogen deficiency may influence susceptibility to oral cancer (C00-06) in women; significantly younger mean age at menopause and higher rates of hysterectomy may influence the high rates of oral cancer reported among younger females [34] .…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, estrogen deficiency has been shown to increase the risk for oral cancer among women. 8,9 The typical HNSCC patient is a 65 year old male with low socioeconomic status and heavy alcohol and smoking habits. However, an alarming trend has been noticed the past years with an increasing number of individuals younger than 45 years of age developing HNSCC.…”
Section: List Of Publicationsmentioning
confidence: 99%
“…[14][15][16] This group calls for further studies but genetic susceptibility 17 and younger mean age at menopause, leading to estrogen deficiency, have been suggested as risk factors. 8,9 In recent years, the human papillomavirus (HPV) type 16 has been associated with cancer in the tonsils and base of tongue in a subset of younger patients with no other reported risk factors.…”
Section: List Of Publicationsmentioning
confidence: 99%